Indian Ocean Region: A Strategic Analysis - Haseeb, Faiza (Journal of Pakistan Administration, 2021)
The Indian Ocean Region (IOR) is the new trend in future. The IOR is internationally recognized as a region of growing geopolitical importance, characterized by competition and intense rivalries involving regional and extra-regional/global powers as well as the littoral states. The strategic environment is volatile and recently has been the focus of increasing global attention. The IOR will decide the future of states in these waters. Three major powers i.e. US, China and India, together accounting for nearly half of the global economy, are vying for influence in the IOR. These powers are engaged in rifts to attain naval and maritime supremacy over one another resulting in complex power struggles, which has implications for Pakistan.